Family & political power in the Paraiba through the book Boy from Engenho, by José Lins do Rego: literature and history under the bias of cultural history - Barros, Queila Guedes Feliciano (Em Perspectiva, 2019)
We propose in this work a brief discussion about the conflictual issues that involve the craft of the historian and its production, starting with the use of literature as a source for history. Historical knowledge is taken into account as a narrative science and practice, based on the analysis of the novel by José Lins do Rego from Paraibano novel "Menino de engenho". In order to do so, we have dialogues with authors that allow us to obtain an extended and profound view of the discussion about truth and fiction that permeate the work of the historian and reflect on the actions of the historian as a method and its production as narrative (text). base reflections on the concept and use of representation versus "historical truth" as a theoretical-methodological apparatus.